Między dziennikarzem a naukowcem. Rola i udział rzecznika prasowego uczelni uniwersyteckiej w komunikowaniu mediów z ekspertami - Boruszczak, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The author explains the specificity of the university press spokesman’s work, and describes ways to connect university experts with the media; he points out the difficulty of this work and proposes solutions.